Political Participation of the Millennial Generation in General Elections: The Influence of Education, Social Media, and Economic Factors - Utari Utari; Yuni Wulandari; Colby Colby; Crespi Crespi (Insan Akademika Publications, 2023)
The Millennial generation, comprising individuals born between the early 1980s and mid-1990s, represents a significant demographic group with the potential to shape the political landscape. This research investigates the multifaceted determinants of Millennial political participation in general elections, seeking to unravel the complexities that drive or hinder their engagement in the democratic process. Employing a mixed-methods approach encompassing surveys and interviews, this study examines key factors influencing Millennial political behavior. The research findings reveal several pivotal insights; Firstly, education emerges as a critical catalyst for Millennial political participation, emphasizing the importance of civic education programs in nurturing political awareness. Secondly, social media platforms, such as Twitter and Facebook, have assumed a transformative role, serving as potent tools for information dissemination, mobilization, and interactive political discourse. Thirdly, economic challenges, notably student loan debt and economic insecurity, persist as formidable barriers, necessitating targeted policies to alleviate these concerns and encourage political engagement. Fourthly, trust in political institutions emerges as a motivating factor, highlighting the significance of transparency and accountability in enhancing Millennial voter turnout. Lastly, non-electoral civic activities, including volunteering and community service, serve as precursors to broader political involvement, underscoring the value of encouraging civic engagement. The implications drawn from these findings reverberate through the realms of policy, political strategy, and societal empowerment. Recommendations include investments in civic education, leveraging social media for political outreach, addressing economic disparities, and fostering civic engagement. As Millennial political participation continues to evolve, this research underscores the importance of empirical analysis in informing effective strategies and policies. It serves as a clarion call for collective action, urging stakeholders across academia, politics, and civil society to empower Millennials as active and informed participants in the democratic process. This research contributes not only to academic knowledge but also to the practical endeavor of strengthening democratic foundations, ensuring that the voices of Millennials resonate within the corridors of governance, and shaping the trajectory of our collective political future